MicroRNA hsa-miR-29b potentiates etoposide toxicity in HeLa cells via down-regulation of Mcl-1 - Kollinerová, S; Dostál, Z; Modrianský, M (Toxicology in vitro, 2017)
Etoposide is commonly used as a monotherapy or in combination with other drugs for cancer treatments. In order to increase the drug efficacy, ceaseless search for novel combinations of drugs and supporting molecules is under way. MiRNAs are natural candidates for facilitating drug effect in various cell types. We used several systems to evaluate the effect of miR-29 family on etoposide toxicity in HeLa cells. We show that miR-29b significantly increases etoposide toxicity in HeLa cells. Because Mcl-1 protein has been recognized as a miR-29 family target, we evaluated downregulation of Mcl-1 protein splicing variant expression induced by miR-29 precursors and confirmed a key role of Mcl-1 protein in enhancing etoposide toxicity. Despite downregulation of Mcl-1 by all three miR-29 family members, only miR-29b significantly enhanced etoposide toxicity. We hypothesized that this difference may be linked to the change in Mcl-1L/Mcl-1S ratio induced by miR-29b. We hypothesized that the change could be due to miR-29b nuclear shuttling. Using specifically modified miR-29b sequences with enhanced cytosolic and nuclear localization we show that there is a difference, albeit statistically non-significant. In conclusion, we show that miR-29b has the synergistic effect with etoposide treatment in the HeLa cells and that this effect is linked to Mcl-1 protein expression and nuclear shuttling of miR-29b.
Keywords: Myeloid Cell Leukemia Sequence 1 Protein; HeLa Cells; protein MCL-1; Mcl-1; Cell Cycle; fytogenní protinádorové látky; lidé; HeLa buňky; xCELLigence; Antineoplastic Agents, Phytogenic; buněčný cyklus; Down-Regulation; etoposid; miR-29; mikro RNA; MicroRNAs; HeLa cells; down regulace; Cell Survival; viabilita buněk; Etoposide; Humans